2014
DOI: 10.4161/gmic.28093
|View full text |Cite
|
Sign up to set email alerts
|

SerpinB2 mediated regulation of macrophage function during enteric infection

Abstract: Host defense is an orchestrated response involving changes in the expression of receptors and release of mediators from both immune and structural cells. There is a growing recognition of the important role of proteolytic pathways for the protective immune response to enteric pathogens. Enteric nematode infection induces a type 2 immune response with polarization of macrophages toward the alternatively activated phenotype (M2). The Th2 cytokines, IL-4, and IL-13, induce a STAT6-dependent upregulation of the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 45 publications
0
15
0
1
Order By: Relevance
“…MRC1 is an innate pattern-recognition receptor and has functions in clearing allergens and limiting allergic inflammation ( 46 ). SerpinB2 represents an immune-regulated factor that is critical for macrophage survival ( 47 ). The increase in molecules increased with FX stimulation indicated that FX may promote macrophages toward the M2 subtype to establish an immunosuppressive environment that is beneficial for tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…MRC1 is an innate pattern-recognition receptor and has functions in clearing allergens and limiting allergic inflammation ( 46 ). SerpinB2 represents an immune-regulated factor that is critical for macrophage survival ( 47 ). The increase in molecules increased with FX stimulation indicated that FX may promote macrophages toward the M2 subtype to establish an immunosuppressive environment that is beneficial for tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…SERPINB2 has been implicated in Th2 responses where it is regulated by STAT6 [10]. Other recognized transcriptional regulators include NFκB, AP-1 and C/EBPβ [11, 12].…”
Section: 0 Introductionmentioning
confidence: 99%
“…SerpinB2 is highly expressed in macrophages, [15][16][17] suggesting a potential role for these or other hematopoietically derived cells in the host responses to B16 melanoma and LLC observed above. To test this hypothesis, BMT was performed into N7 SerpinB2 −/− recipients and age and sex-matched WT littermate controls using either donor Figure 2B).…”
Section: The Optimal Host Response To Injected B16 Melanoma or Llc mentioning
confidence: 94%